Mycotic Abdominal Pseudoaneurysm due to Psoas Abscess after Spinal Fusion - Ryu, Dae Woong (Korean J Thorac Cardiovasc Surg, 2015)
A 36-year-old man, who had undergone thoracoscopic anterior spinal fusion using the plate system and posterior screw fusion three months previously, presented to our hospital with left flank pain and fever. Computed tomography indicated the presence of a psoas muscle abscess. However, after two days of percutaneous catheter drainage, a mycotic abdominal aortic pseudoaneurysm was detected via computed tomography. We performed in situ revascularization using a prosthetic graft with omental wrapping. Methicillin-resistant Staphylococcus aureus was identified on blood and pus culture, and systemic vancomycin was administered for one month. Although the abscess recurred, it was successfully treated with percutaneous catheter drainage and systemic vancomycin administration for three months, without the need for instrumentation removal. The patient remained asymptomatic throughout two years of follow-up.